Seed transmission of maize downy mildew (Peronosclerospora sorghi) in Nigeria - Adenle, V.O.; Cardwell, K.F. (Wiley, 2000)
In an area of Nigeria where downy mildew of maize is present, histological assessment of maize seed revealed the presence of mycelium and oospores of Peronosclerospora sorghi in the kernels. Seed transmission of downy mildew of maize was demonstrated when grain purchased at local markets gave mean seedling infection rates of 12•3% (untreated days of emergence, after storage seeds) and 10•0% (in metalaxyl‐treated seeds) within 7 days. When untreated seeds taken from nubbin ears of systemically in a desiccator for 30 days (17–22% infected plants from four states in southern Nigeria were planted at 9 days (9–22% moisture content) after harvest, 20•0% infected moisture content) and 27 seedlings resulted in both trials. Seeds from Borno state in northern Nigeria had months of storage at 11% moisture content. 26•6% systemic seedling infection after 9 When seeds harvested from maize plants inoculated with P. sorghi through silks were examined histologically, hyphae of P. sorghi were observed mostly in the scutellum of the embryo. Transmission of disease to seedlings was observed when the silk‐inoculated seeds (9% moisture content) were planted in pots in a greenhouse; however, no disease transmission was observed when such seeds were planted in the field. The epidemiological significance of seed transmission is discussed with particular reference to survival of inoculum and development of epidemics. Also noteworthy is the overall significance of seed transmission in Nigeria, where the major source of seed is that saved by farmers from their grain crop, occasionally supplemented by seed bought from the local market.